Strategi Pemasaran Tabungan Junior di PT. Bank Syariah Indonesia KCP Medan Marelan - Perdana Siregar, Anri Akta; Atika, Atika (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Junior savings service is currently one of the service the best provided by the bank to support bank operasional activities become more effective and efficient. The goal is to facilitate the performance of a product bank service, so as to increase customers based on the number of customers of Bank syariah indonesian users of Junior savings reached around 50% responding to this, Bank Syariah indonesian seeks to improve and mainttain the quality of service provided to attract customers. The problem in this research what is the Bank’s strategy that is an obstacle to improving the quality of Junior savings service. The purpose of this research is to find out the strategy of Bank Syariah indonesian in improving service quality and to find out what are the obstacles for Bank Syariah indonesian in improving the quality of junior savings services and to find out what are the solutions for Bank Syariah indonesian in facing obstacles to improve the quality junior savings services. Banking. The method used in this research is a field study, this method is used to find out how far the suitability between the theories used is with the actual situation of the object under study. In this field study using interviews and observation. And the type of research used is descriptive qualitative research as a whole it can be concluded from this research is the strategy of Bank Syariah Indonesian in improving service quality, namely launching "New junior savings Bank Syariah indonesian".